POstLAparoscopic Reduction of pain By combining intraperitoneal normal salinE And the pulmonary Recruitment maneuver (POLAR BEAR trial). RCT to estimate reduction in pain after laparoscopic surgery when using a combination therapy of intraperitoneal normal saline and the pulmonary recruitment maneuver - J. E. W. van Dijk; S. J. Dedden; P. M. A. J. Geomini; P. Meijer; N. van Hanegem; M. Y. Bongers (BMC, 2017)
Abstract Background Shoulder pain and pain in the upper abdomen are common complaints after laparoscopy, sometimes surpassing the pain at incision sites. The incidence of shoulder pain ranges from 35 to 80%. Post-laparoscopic pain is caused by retention of carbon dioxide in the abdomen, which irritates the phrenic nerve and diaphragm, causing referred pain in the shoulder and in the upper abdomen. A promising strategy to reduce this post-laparoscopic pain is the pulmonary recruitment maneuver, which indirectly increases intraperitoneal pressure and thereby facilitates removal of residual carbon dioxide. An alternative strategy is the infusion of intraperitoneal normal saline. With normal saline infusion, carbon dioxide rises and escapes through the port sites. In addition, normal saline offers a physiologic buffer system to dissolve excess carbon dioxide. Methods/Design This multicenter randomized controlled trial is conducted in two teaching hospitals in the Netherlands. Women between 18 and 65 years of age, with an ASA classification of I-II who are scheduled to undergo an elective laparoscopic procedure with benign gynecologic indication can participate. Following informed consent, participants are randomly allocated into two groups at the end of the surgical procedure. In the intervention group, the upper abdomen is filled with normal saline infusion with the patient in the Trendelenburg position. Then the anesthesiologist performs a standardized pulmonary recruitment maneuver with a pressure of 40 cm H2O. The trocar sleeve valves will be left open, so carbon dioxide can escape the abdominal cavity. With the patient in a neutral position the instruments are removed from the abdomen. In the control group, carbon dioxide is removed from the abdominal cavity at the end of surgery, with gentle abdominal pressure and passive exsufflation through the port sites, with open sleeve valves. The primary outcomes are the incidence and intensity of post-laparoscopic pain in the shoulder, upper abdomen and at the operation sites, at 8, 24 and 48 h after surgery. Secondary outcomes are postoperative use of analgesics, nausea, vomiting and pulmonary complications. Discussion This study may reduce post-laparoscopic pain in women undergoing laparoscopy. Trial registration Dutch trial register, number NTR4812 .